Mechanochemically synthesized covalent organic framework as a proton-conducting solid electrolyte - Shinde, Digambar Balaji; Aiyappa, Harshitha Barike; Bhadra, Mohitosh; Biswal, Bishnu P.; Wadge, Pritish; Kandambeth, Sharath; Garai, Bikash; Kundu, Tanay; Kurungot, Sreekumar; Banerjee, Rahul (Journal of Materials Chemistry A, 2016)
Mechanochemistry has become an increasingly important synthetic tool for a waste-free environment. However, the poor quality of the so-derived materials in terms of their crystallinity and porosity has been their major drawback for any practical applications. In this report, we have for the first time successfully leveraged such characteristics to show that the mechanochemically synthesized bipyridine based covalent organic framework (COF) outperforms its conventional solvothermal counterpart as an efficient solid-state electrolyte in PEM fuel cells. Marking the first such attempt in COFs, a Membrane Electrode Assembly (MEA) fabricated using the mechanochemically synthesized COF was observed to inhibit the fuel crossover and build up a stable Open Circuit Voltage (OCV = 0.93 V at 50 degrees C), thereby establishing itself as an effective solid electrolyte material (with a proton conductivity of 1.4 x 10(-2) S cm(-1)), while the solvothermally synthesized COF proved ineffective under similar conditions.

Magnetic reduced graphene oxide loaded hydrogels: highly versatile and efficient adsorbents for dyes and selective Cr(VI) ions removal - Halouane, Fatima; Oz, Yavuz; Meziane, Dalila; Barras, Alexandre; Juraszek, Jean; Singh, Santosh K.; Kurungot, Sreekumar; Shaw, Pankaj K.; Sanyal, Rana; Boukherroub, Rabah; Sanyal, Amitav; Szunerits, Sabine (Journal of Colloid and Interface Science, 2017)
The formation of composites of reduced graphene oxide (rGO) and magnetic nanoparticles (MP) has flourished in recent years as they combine the advantages of both nanomaterials. Most of these composite materials are prepared by in situ formation of MP onto rGO or by the post-adsorption onto rGO. We report here on a simple and highly controlled method for the fabrication of different magnetic 3D rGO-loaded hydrogels. Cellulose bound magnetic nanoparticles (MP@cellulose) were synthesized by chemical co-precipitation and loaded together with rGO into poly(ethylene glycol) dimethacrylate based hydrogels during their fabrication using photo-polymerization. The magnetic rGO-loaded hydrogels proved to be highly adaptable to different applications. The as-formed composites allowed for efficient dye removal with an adsorption capacity of 111.9 +/- 4 mg g(-1) in the case of methylene blue (MB). Integration of poly(ethyleneimine) (PEI) allowed for the selective capturing of Cr6+ ions with an adsorption capacity of 313 12 mg g-1. Most importantly, independent of the application, the magnetic rGO-loaded hydrogel can be regenerated without loss of its adsorption capacity. (C) 2017 Elsevier Inc. All rights reserved.

Melamine formaldehyde-metal organic gel interpenetrating polymer network derived intrinsic Fe-N-doped porous graphitic carbon electrocatalysts for oxygen reduction reaction - Shijina, Kottarathil; llathvalappil, Rajith; Sumitha, N. S.; Sailaja, G. S.; Kurungot, Sreekumar; Nair, Balagopal N.; Mohamed, A. Peer; Anilkumar, Gopinathan M.; Yamaguchig, Takeo; Hareesh, U. S. (New Journal of Chemistry, 2018)
Fe, N doped porous graphitic carbon electrocatalyst (Fe-MOG-MF-C), obtained by pyrolysis of an Interpenetrating Polymer Network (IPN) comprised of melamine formaldehyde (MF as hard segment) and Metal-Organic Gel (MOG as soft segment), exhibited significant Oxygen Reduction Reaction (ORR) activity in alkaline medium. BET surface area analysis of Fe-MOG-MF-C showed high surface area (821 m(2) g(-1)), while TEM, Raman and XPS results confirmed Fe and N co-doping. Furthermore, a modulated porous morphology with a higher degree of surface area (950 m(2) g(-1)) has been accomplished for the system (Fe-MOG-MFN-C) when aided by a sublimable porogen, such as naphthalene. XPS results further demonstrated that these systems exhibited a better degree of distribution of graphitic N and an onset potential value of 0.91 V vs. RHE in 0.1 M KOH solution following an efficient four-electron ORR pathway. The electrocatalytic activity of Fe-MOG-MFN-C is superior to that of Fe-MOG-MF-C by virtue of its higher graphitic N content and surface area. Thus, the study presents a new class of IPN derived MF-MOG nanocomposites with the potential to generate extended versions of in situ Fe-N doped porous graphitic carbon structures with superior ORR activity.

Morphological ensembles of N-doped porous carbon derived from ZIF-8/Fe-graphene nanocomposites: processing and electrocatalytic studies - Thomas, Minju; Illathvalappil, Rajith; Kurungot, Sreekumar; Nair, Balagopal N.; Mohamed, A. Peer; Anilkumar, Gopinathan M.; Yamaguchi, Takeo; Hareesh, U. S. (ChemistrySelect, 2018)
Engineering the active site density of porous carbon catalysts for enhanced electrocatalytic activity is the current focus in the quest for economically viable fuel cells. Herein, we synthesise ZIF-8/Fe-graphene composites for the formation of N and Fe co-doped carbon with diverse morphologies ranging from tubes and sheets to frameworks of carbon. A synthetic strategy involving the one pot synthesis of ZIF-8 based composites is accomplished by the reaction of 2-methylimidazole with mixed Zn/Fe salt solution containing graphene dispersions. The high temperature heat treatment of this precursor mix yielded micro-meso porous architectures of N, Fe co-doped carbon with dispersions of Fe/Fe3C. An onset potential value of 0.95 V and a half-wave potential of 0.82 V coupled with excellent durability and stability in alkaline medium indicated improved electrocatalytic performances over its commercial Pt/C counterpart. The appreciable electrocatalytic properties of the synthesized carbon are attributed to its morphological diversity, hybrid structure, high N doping and its heteroporous characteristics. The dispersed Fe/Fe3C and FeNx sites facilitated enhanced oxygen adsorption and the graphene inclusions in the composite provided retention of high nitrogen contents.
Keywords: electrocatalyst; fuel cell; N- Fe co-doped carbon; oxygen reduction reaction; ZIF-8

[MoS4](2-)-Intercalated NiCo-layered double hydroxide nanospikes: an efficiently synergized material for urine to direct H-2 generation - Nadeema, Ayasha; Kashyap, Varchaswal; Gururaj, Rakshitha; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2019)
Substituting the energy-uphill water oxidation half-cell with readily oxidizable urea-rich urine, a ground-breaking bridge is constructed, combining the energy-efficient hydrogen generation and environmental 6 protection. Hence, designing a robust multifunctional electrocatalyst is desirable for widespread implementation of this waste to fuel technology. In this context, here, we report a simple tuning of the electrocatalytically favorable characteristics of NiCo-layered double hydroxide by introducing [MoS4]2- in its interlayer space. The [MoS4]' insertion as well as its effect on the electronic structure tuning is thoroughly studied via X-ray photoelectron spectroscopy in combination with electrochemical analysis. This insertion induces overall electronic structure tuning of the hydroxide layer in such a way that the designed catalyst exhibited favorable kinetics toward all the required reactions of hydrogen generation. This is why our homemade catalyst, when utilized both as a cathode and anode to fabricate a urea electrolyzer, required a mere X1.37 V cell potential to generate sufficient H2 by reaching the benchmark 10 mA cm-2 in 1 M KOH/0.33 M urea along with long-lasting catalytic efficiency. Other indispensable reason of selecting [MoS4]2- is its high-valent nature making the catalyst highly selective and insensitive to common catalyst-poisoning toxins of urine. This is experimentally supported by performing the real urine electrolysis, where the nanospike-covered Ni foam-based catalyst showed a performance similar to that of synthetic urea, offering its industrial value. Other intuition of selecting [MoS4]2- was to provide a ligand-based mechanism for hydrogen evolution half-cell [hydrogen evolution reaction (HER)] to preclude the HER-competing oxygen reduction. Another crucial point of our work is its potential to avoid the mixing of two explosive product gases, that is, H2 and O-2.
Keywords: hydrogen evolution reaction; Layered double hydroxide; nickel oxyhydroxide; sewage denitrification; urea oxidation reaction; urine/urea electrolysis

Microporous 3D-structured hierarchically entangled graphene-supported Pt3Co alloy catalyst for PEMFC application with process-friendly features - Manna, Narugopal; Singh, Mayank; Kurungot, Sreekumar (ACS Applied Materials & Interfaces, 2023)
To improve the oxygen reduction reaction(ORR) performance in aproton-exchange membrane fuel cell (PEMFC) cathode with respect tomass activity and durability, a suitable electrocatalyst design strategyis essentially needed. Here, we have prepared a sub-three nm-sizedplatinum (Pt)-cobalt (Co) alloy (Pt3Co)-supportedN-doped microporous 3D graphene (Pt3Co/pNEGF) by usingthe polyol synthesis method. A microwave-assisted synthesis methodwas employed to prepare the catalyst based on the 3D porous carbonsupport with a large pore volume and dense micro-/mesoporous surfaces.The ORR performance of Pt3Co/pNEGF closely matches withthe state-of-the-art commercial Pt/C catalyst in0.1 M HClO4, with a small overpotential of 10 mV. The 3Dmicroporous structure of the N-doped graphene significantly improvesthe mass transport of the reactant and thus the overall ORR performance.As a result of the lower loading of Pt in Pt3Co/pNEGF ascompared to that in Pt/C, the alloy catalyst achieved 1.5 times highermass activity than Pt/C. After 10,000 cycles, the difference in theelectrochemically active surface area (ECSA) and half-wave potential(E (1/2)) of Pt3Co/pNEGF is foundto be 5 m(2) g(Pt) (-1) (Delta ECSA)and 24 mV (Delta E (1/2)), whereas, forPt/C, these values are 9 m(2) g(Pt) (-1) and 32 mV, respectively. Finally, in a realistic perspective, single-celltesting of a membrane electrode assembly (MEA) was made by sandwichingthe Pt3Co/pNEGF-coated gas diffusion layers as the cathodedisplayed a maximum power density of 800 mW cm(-2) under H-2-O-2 feed conditions with aclear indication of helping the system in the mass-transfer region(i.e., the high current dragging condition). The nature of the I-V polarization shows a progressivelylower slope in this region of the polarization plot compared to asimilar system made from its Pt/C counterpart and a significantlyimproved performance throughout the polarization region in the caseof the system made from the Pt3Co/NEGF catalyst (withoutthe microwave treatment) counterpart. These results validate the betterprocess friendliness of Pt3Co/pNEGF as a PEMFC electrode-specificcatalyst owing to its unique texture with 3D architecture and well-definedporosity with better structural endurance.
Keywords: microwave synthesis; N-doped porous 3D graphene; ORR; PEMFC; polyol synthesis; Pt3Co alloy